An Unusual Presentation of Pleomorphic Lipoma. (28th October 2020) - Smith, F; Martinez Duarte, E
Abstract: Introduction/Objective: Pleomorphic lipomas are benign tumors that typically occur in the shoulder, posterior neck, and back. Here, we present a case of a pleomorphic lipoma arising in an unusual location. Methods: A 63-year-old male presented with a 1.3 x 1.3 x 0.9 cm enhancing slightly heterogeneous mass in the subcutaneous tissue superficial to the right parotid tail. The mass was biopsied and then excised. Results: Histopathologic examination of the biopsy and resection specimens revealed an adipocytic neoplasm composed of mature adipose tissue with admixed spindle cells within a myxoid stroma. Lipoblasts, cellular atypia or increased mitotic figures were absent. Numerous floret-like cells were identified. These floret cells are characteristic of pleomorphic lipoma. The tumor cells were diffusely positive for CD34 and negative for desmin, smooth muscle actin, MyoD1, keratin, SOX10, and Melan-A by immunohistochemistry, consistent with pleomorphic lipoma. Conclusion: Pleomorphic lipomas arising from the periparotid adipose tissue are rare. They tend to have a favorable prognosis with low incidence of recurrence if excised with clear margins. Following complete excision, the patient is doing well.